2013
DOI: 10.1111/jora.12079
|View full text |Cite
|
Sign up to set email alerts
|

Coping With LGBT and Racial–Ethnic‐Related Stressors: A Mixed‐Methods Study of LGBT Youth of Color

Abstract: This study examines how racial-ethnic minority lesbian, gay, bisexual, and transgender (LGBT) youth cope with both racial-ethnic and LGBT-related stress. Within a sample of 213 LGBT youth of color, the present study presents (1) quantitative and qualitative results from an approach and avoidance-based measure of parental racial coping socialization across six conversation domains, and (2) qualitative responses regarding LGBT stressors and associated coping strategies. The emphasis on approach versus avoidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 65 publications
3
53
0
Order By: Relevance
“…The efficacy of these approaches, however, was not considered. A very recent study by Goldbach and Gibbs (2015) examined how sexual minority youth cope with minority stress; consistent with the findings by Kuper and colleagues (2014), youth in the Goldbach and Gibbs (2015) study commonly endorsed avoidant coping strategies.…”
Section: Coping With Minority Stressmentioning
confidence: 59%
“…The efficacy of these approaches, however, was not considered. A very recent study by Goldbach and Gibbs (2015) examined how sexual minority youth cope with minority stress; consistent with the findings by Kuper and colleagues (2014), youth in the Goldbach and Gibbs (2015) study commonly endorsed avoidant coping strategies.…”
Section: Coping With Minority Stressmentioning
confidence: 59%
“…Yet other reports have not found racial-ethnic differences in level of disclosure (Boxer, Cook, & Herdt, 1991; Ryan et al, 2009). Across all racial-ethnic groups, youths discussed fear of disclosure because of potential for rejection, and parental reactions to disclosure included both acceptance and rejection (Aleman, 2005; Balaji et al, 2012; Coffey, 2008; Follins, 2003; Hunter, 1990; Kuper, Coleman, & Mustanski, 2014; Munoz-Laboy et al, 2009; Reck, 2009; Timm et al, 2013; Voisin et al, 2013; Yon-Leau & Munoz-Laboy, 2010). Only one report found a significant difference in experienced parental acceptance after disclosure, in that Black participants reported less acceptance than Latino or White youth (Coffey, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Other research has demonstrated that sexual identity affirmation is meaningful for the well-being of sexual minorities (Ghavami, Fingerhut, Peplau, Grant, & Wittig, 2011). Yet only seven studies examined these co-occurring processes for SMYoC (Hidalgo et al, 2013; Hunter, 1996; Jamil & Harper, 2010; Kuper et al, 2014; Langdon, 2009; Stevens et al, 2013; Vu et al, 2011). Thus, research focused on SMYoC needs to attend to these normative co-occurring developmental processes, particularly during early adolescence (Herdt & McClintock, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…59,60 Providers also need to ensure that services are inclusive of and sensitive to the needs of diverse racial/ethnic groups of LGBTQ youth, including those of color and who are non-native English speaking patients. 61 Finally, providers should ensure that services are provided to all LGBTQ youth regardless of ability to pay. Many youth, particularly those without legal immigrant status in the United States, without health insurance, or without stable housing are likely to have unmet health needs.…”
Section: Systems-level Principles Underlying Lgbtq Youth-friendly Sermentioning
confidence: 99%